Protective Roles of Green Extract Zinc Oxide Nanoparticles on Monosodium Glutamate-Induced Hepatotoxicity and Nephrotoxicity in Female Rats. - Azheen Abdulrahman; Shang Abdulqadir; Inaam Mustafa (مجلة التربية والعلم)
Monosodium glutamate (MSG) is the sodium salt of glutamic acid, it’s noxious to human and experimental animals. Nowadays, Zinc oxide nanoparticles (ZnO-NPs) are among the most widely used metal oxide nanoparticles in biological applications because of their cost-effectiveness and superior biocompatibility. Current research aims to assess ZnO-NPs protective effect against MSG-induced hepatotoxicity and nephrotoxicity in rats. In the present investigation, 16 female mature rats were randomly distributed over four groups. The rats of the first group were daily received 1 ml normal saline intraperitoneally, the rats of second group were administrated with 4 mg/kg MSG by gavage, the rats of third group were administrated with 10 mg/kg ZnO-NPs intraperitoneally, and the rats of fourth group were administrated with the mixture of the MSG/ZnO-NPs. After 14 days, all rats were weighed; then, the liver and kidneys were processed using histopathological techniques, and blood specimens were used for biochemical analysis. MSG generated various histological changes in liver tissues, including hepatocyte deterioration, inflammation, and vascular congestion.Regarding the kidney, certain histological alterations, such as a contracted glomerulus, inflammatory infiltration, congestion, and tubule dilatation following MSG treatment, were detected. Regarding biochemical parameters, MSG elevated each AST, ALT, ALP, urea, and MDA level. More importantly, ZnO-NPs could decrease the negative influences of histological and biochemical changes that MSG causes in both the liver and kidney of rats. ZnO-NP therapy improved the aberrant histological changes in the liver and kidneys caused by MSG.